2018
DOI: 10.1186/s12958-018-0339-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exposure to CeO2 nanoparticles on ram spermatozoa during storage at 4 °C for 96 hours

Abstract: BackgroundCerium oxide nanoparticles (CeO2 NPs) are able to store and release oxygen, conferring them scavenger activity against oxidative stress. However, their effects in reproductive systems are not yet well understood. The aim of the study was to investigate the effects of exposure of refrigerated ram semen to CeO2 NPs for 96 h on the main structural and kinematic parameters of spermatozoa.MethodsThe ejaculates of 5 Sarda rams were collected, pooled and diluted in a soybean lecithin extender. Samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…Consequently, the CUNPs can mitigate OS injury through down-regulation of the H2O2 level and protect the spermatozoa from being injured by inflammatory factors, to achieve the purpose of protecting the sperm quality [ 36 ]. Furthermore, Falchi et al [ 37 ] have revealed the antioxidant capability of cerium oxide (CeO2) nanoparticles on ram spermatozoa during storage at 4 °C. This might be related to the amounts of ROS were reduced within the semen extender through storage, which explained into better motion features and sperm viability.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the CUNPs can mitigate OS injury through down-regulation of the H2O2 level and protect the spermatozoa from being injured by inflammatory factors, to achieve the purpose of protecting the sperm quality [ 36 ]. Furthermore, Falchi et al [ 37 ] have revealed the antioxidant capability of cerium oxide (CeO2) nanoparticles on ram spermatozoa during storage at 4 °C. This might be related to the amounts of ROS were reduced within the semen extender through storage, which explained into better motion features and sperm viability.…”
Section: Discussionmentioning
confidence: 99%
“…The supplementation of semen extenders with antioxidant substances could reduce the deleterious effects of the higher production of ROS and oxidative stress on sperm cells (Falchi, Galleri, Dore et al, ). Melatonin and its metabolites are known as antioxidants and potent free radical scavengers (Harderland et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of CeO 2 in semen extender improved motility parameters after 48 h and up to 96 h of incubation and increased sperm velocity of sperm cells. This was associated with protecting the integrity of plasma membranes and DNA of spermatozoa [12]. These effects could not be linked with any reduction in intracellular ROS as detected by H2DCFDA staining [12], however, the sensitivity of this cytoplasmic stain may not be sufficient to detect minor differences in sperm cells due to the cellular structure of the sperm head which is mostly occupied by a nucleus.…”
Section: Effects Of Nps As Antioxidants On Sperm Functionsmentioning
confidence: 98%
“…Semen cooling and cryopreservation are known to increase oxidative stress in spermatozoa leading to a significant reduction in their fertilization capacity [11]. We have recently tested the efficiency of cerium oxide (CeO 2 ) NPs, which are able to store oxygen and act as ROS (reactive oxygen species) scavengers, to protect ram sperm cell viability during cooling [12]. Supplementation of CeO 2 in semen extender improved motility parameters after 48 h and up to 96 h of incubation and increased sperm velocity of sperm cells.…”
Section: Effects Of Nps As Antioxidants On Sperm Functionsmentioning
confidence: 99%